Investigation of discrepancies in isotropic material and structural properties in lattice frameworks - Ahmad Anas Arifin; I Made Londen Batan; Michele Bici; Arif Wahjudi; Agus Sigit Pramono (Mechanical Engineering for Society and Industry, 2025)
Lattice structures have developed as a vital component in advanced engineering applications due to their superior strength-to-weight ratios and adjustable mechanical properties. This paper focuses on examining the correlation between the isotropic features of lattices at the material level and their structural performance. The research used near-isotropic Crossing-cylinder (CC)- Body Centered Cubic (BCC) cells in various orientations and sizes. Both experimental analysis and finite element analysis were used to examine the compressive strength of the structure in each orientation. The results reveal that cell orientation is important for determining failure modes and mechanical performance at the structural level. At 0°, the lattice has higher compressive strength and energy absorption due to effective load transfer via CC-aligned struts. In contrast, higher orientations (e.g., 15°, 30°, and 45°) are dominated by collapse-type failures, indicating anisotropic behavior in an otherwise isotropic design. Smaller cell sizes have more strength at lower orientations due to their higher relative density, but larger cells perform better at higher orientations.